Decreased risk for substance use disorders in individuals with high-functioning autism spectrum disorder - Yule, Amy M.; DiSalvo, Maura; Biederman, Joseph; Wilens, Timothy E.; Dallenbach, Nina T.; Taubin, Daria; Joshi, Gagan (European child & adolescent psychiatry, 2023)
The objective of this study was to evaluate the risk for developing a substance use disorder (SUD, alcohol or drug abuse or dependence) in individuals with high-functioning autism spectrum disorder (ASD). Subjects with high-functioning ASD were derived from consecutive referrals to a specialized ambulatory program for ASD at a major academic center from 2007 to 2016. Age-matched controls and attention-deficit hyperactivity disorder (ADHD) comparison subjects were derived from three independent studies of children and adults with and without ADHD using identical assessment methodology. Cox proportional hazard models were used to analyze the prevalence of SUD (alcohol or drug use disorder). Age of onset of SUD was analyzed with linear regression models. Our sample included 230 controls, 219 subjects with ADHD, and 230 subjects with ASD. The mean age for the ASD subjects was 20.0 ± 10.3 years. Among ASD subjects, 69% had a lifetime prevalence of ADHD, and the ASD subjects had significantly higher rates of other psychiatric psychopathology compared to ADHD and control subjects ( p < 0.001) ASD subjects were at significantly decreased risk for developing a SUD compared to ADHD (hazard ratio (HR) = 0.22, p < 0.001) and control subjects (HR = 0.62, p = 0.04). The age of onset of a SUD was significantly older in ASD subjects, mean age 21.7 years, when compared to ADHD and control subjects (both p < 0.005). Individuals with ASD are at decreased risk to develop a SUD, and when they do, the onset is significantly later than ADHD and controls.